Adiponectin synthesis and secretion by subcutaneous adipose tissue is impaired during obesity by endoplasmic reticulum stress. Issue 7 (25th March 2018) - Torre‐Villalvazo, Ivan; Bunt, Ana E.; Alemán, Gabriela; Marquez‐Mota, Claudia C.; Diaz‐Villaseñor, Andrea; Noriega, Lilia G.; Estrada, Isabela; Figueroa‐Juárez, Elizabeth; Tovar‐Palacio, Claudia; Rodriguez‐López, Leonardo A.; López‐Romero, Patricia; Torres, Nimbe; et al.
Abstract: Subcutaneous (SAT) and visceral (VAT) adipose tissues stores excess energy as triglycerides and synthesize adiponectin to prevent ectopic lipid accumulation and lipotoxicity. During obesity, an impairment in the capacity of SAT to store triglycerides and synthesize adiponectin is associated with increased free fatty acids (FFA) release, leading to VAT hypertrophy and hepatic and skeletal muscle lipotoxicity. Endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) may be involved in SAT dysfunction during obesity. The objectives of this study were to assess UPR activation and adiponectin synthesis in: 1) SAT and VAT from mice exposed to acute pharmacologic or chronic obesity‐induced ER stress and in 2) cultured mice primary mature adipocytes or adipocytes differentiated in vitro from SAT and VAT exposed to tunicamycin or thapsigargin. Mice fed a high‐fat diet developed obesity, increased FFA and lower circulating adiponectin in association with lower adiponectin synthesis and increased UPR markers in SAT. Mice subjected to acute ER stress by pioglitazone administration and a low‐dose tunicamycin injection presented a maladaptive UPR activation in SAT along with reduced adiponectin synthesis and secretion and increased lipolysis with respect to VAT, associated with lipid accumulation in skeletal muscle and liver. Primary adipocytes and adipocytes differentiated from SAT exposed to pharmacologic ER stress also developed maladaptive UPR, along with reduced adiponectin synthesis and increased lipolysis with respect to those from VAT. Our results indicate that compared to VAT, SAT is more susceptible to ER stress, leading to increased lipolysis and reduced adiponectin synthesis and secretion. Abstract : Endoplasmic reticulum stress induced a maladaptive UPR in subcutaneous adipose tissue or subcutaneous adipocytes with respect to visceral adipose tissue or visceral adipocytes. Maladaptive UPR was associated with reduced adiponectin synthesis and secretion and increased lipolysis in subcutaneous adipose tissue or subcutaneous primary or differentiated adipocytes with respect to visceral adipose tissue or visceral adipocytes. Subcutaneous maladaptive UPR was associated with metabolic inflexibility and lipid accumulation in skeletal muscle and liver.